An Improved Theoretical Approach to Study Electromagnetic Waves through Fiber Bragg Gratings - Pedro Pereyra (Advances in Condensed Matter Physics)
We show that using the theory of finite periodic systems we obtain an improved approach to calculate transmission coefficients and transmission times of electromagnetic waves propagating through fiber Bragg gratings. We discuss similarities, advantages, and differences between this approach and the well known less accurate one coupled mode approximation and the pseudo-Floquet Mathieu functions approach.